A conceptual foundation for expectations of corporate responsibility. (6th February 2017) - Olkkonen, Laura
Abstract : Purpose: Ability to identify and meet stakeholder expectations is seen as imperative for succeeding in corporate responsibility (CR). However, the existing literature of CR communication treats expectations predominantly as positive constructions. The purpose of this paper is to address this positivity bias and offer insights for a more profound conceptual and empirical understanding of stakeholder expectations. Design/methodology/approach: The paper presents findings from a targeted literature search and empirical illustrations from a thematic analysis of interview data with a focus on the media sector. Findings: The conceptual understanding of expectations is advanced by exploring positive (optimistic and hopeful) and negative (cynical and pessimistic) expectations. The empirical examples portray expectation analysis and how it becomes more complex when expectations turn negative. Research limitations/implications: The data are limited to one sector but implications are discussed with a wider lens to aid future studies in addressing expectations of CR with less positivity bias and, instead, with more conceptual and empirical precision. Practical implications: The identification of different expectation types can help practitioners to map and analyze stakeholder expectations of CR, assess interlinking between positive and negative issues, and address stakeholder criticism in a meaningful way. Social implications: A more precise understanding of stakeholder expectations has the potential to make organizations more sensitive to their societal context, especially concerning CR as social connectedness. Originality/value: The paper addresses a gap in current literature concerning the positivity bias of expectations and offers conceptual and empirical tools for future research and practice.